|
|
Line 103: |
Line 103: |
| </math> | | </math> |
| | | |
− | ==Components== | + | ==Components (angular)== |
| For arbitrary 3D scattering vectors, the [[momentum transfer]] components are: | | For arbitrary 3D scattering vectors, the [[momentum transfer]] components are: |
| :<math> | | :<math> |
Line 154: |
Line 154: |
| = & \frac{\cos \theta_f \cos \alpha_f }{ \sqrt{ \cos^2 \alpha_f (\cos^2 \theta_f + \sin^2 \theta_f) + \sin^2 \alpha_f }} \\ | | = & \frac{\cos \theta_f \cos \alpha_f }{ \sqrt{ \cos^2 \alpha_f (\cos^2 \theta_f + \sin^2 \theta_f) + \sin^2 \alpha_f }} \\ |
| = & \cos \theta_f \cos \alpha_f | | = & \cos \theta_f \cos \alpha_f |
| + | \end{alignat} |
| + | </math> |
| + | |
| + | ==Components (distances)== |
| + | :<math> |
| + | \begin{alignat}{2} |
| + | \mathbf{q} & = \frac{2 \pi}{\lambda} \begin{bmatrix} \sin \theta_f \cos \alpha_f \\ \cos \theta_f \cos \alpha_f - 1 \\ \sin \alpha_f \end{bmatrix} \\ |
| + | & = \frac{2 \pi}{\lambda} \begin{bmatrix} \sin \left( \arctan\left[ \frac{x}{d} \right] \right) \cos \left( \arctan \left[ \frac{z }{d / \cos \theta_f} \right] \right) \\ \cos \left( \arctan\left[ \frac{x}{d} \right] \right) \cos \left( \arctan \left[ \frac{z }{d / \cos \theta_f} \right] \right) - 1 \\ \sin \left( \arctan \left[ \frac{z }{d / \cos \theta_f} \right] \right) \end{bmatrix} \\ |
| + | |
| + | & = \frac{2 \pi}{\lambda} \begin{bmatrix} |
| + | \frac{x/d}{\sqrt{1+\left(x/d \right)^2}} \frac{d}{\sqrt{d^2+z^2\cos^2 \theta_f}} \\ |
| + | \frac{1}{\sqrt{1+\left(x/d \right)^2}} \frac{d}{\sqrt{d^2+z^2\cos^2 \theta_f}} - 1 \\ |
| + | \frac{z \cos \theta_f}{\sqrt{d^2+z^2 \cos^2 \theta_f }} \end{bmatrix} \\ |
| + | |
| + | & = \frac{2 \pi}{\lambda} \begin{bmatrix} |
| + | \frac{x d}{\sqrt{d^2+x^2 }} \frac{1}{\sqrt{d^2+z^2\cos^2 \theta_f}} \\ |
| + | \frac{d}{\sqrt{d^2+x^2}} \frac{d}{\sqrt{d^2+z^2\cos^2 \theta_f}} - 1 \\ |
| + | \frac{z \cos \theta_f}{\sqrt{d^2+z^2 \cos^2 \theta_f }} \end{bmatrix} \\ |
| + | |
| + | \end{alignat} |
| + | </math> |
| + | Note that <math>\cos \theta_f = d/\sqrt{d^2+x^2}</math>, and <math>\cos^2 \theta_f = d^2/(d^2+x^2)</math> so: |
| + | :<math> |
| + | \begin{alignat}{2} |
| + | \frac{1}{\sqrt{d^2+z^2 \cos^2 \theta_f }} |
| + | & = \frac{1}{\sqrt{d^2+z^2 \left( d^2/(d^2+x^2) \right) }} \\ |
| + | & = \frac{1}{\sqrt{d^2} \sqrt{((d^2+x^2)+z^2)/(d^2+x^2) }} \\ |
| + | & = \frac{\sqrt{d^2+x^2}}{d \sqrt{d^2 + x^2 + z^2 }} \\ |
| + | |
| + | \end{alignat} |
| + | </math> |
| + | And: |
| + | :<math> |
| + | \begin{alignat}{2} |
| + | \mathbf{q} |
| + | & = \frac{2 \pi}{\lambda} \begin{bmatrix} |
| + | \frac{x d}{\sqrt{d^2+x^2 }} \frac{\sqrt{d^2+x^2}}{d \sqrt{d^2 + x^2 + z^2 }} \\ |
| + | \frac{d}{\sqrt{d^2+x^2}} \frac{d \sqrt{d^2+x^2}}{d \sqrt{d^2 + x^2 + z^2 }} - 1 \\ |
| + | \frac{z \left( d/\sqrt{d^2+x^2} \right) \sqrt{d^2+x^2}}{d \sqrt{d^2 + x^2 + z^2 }} \end{bmatrix} \\ |
| + | |
| + | & = \frac{2 \pi}{\lambda} \begin{bmatrix} |
| + | \frac{x}{ \sqrt{x^2 + d^2 + z^2 }} \\ |
| + | \frac{d }{\sqrt{x^2 + d^2 + z^2 }} - 1 \\ |
| + | \frac{z }{\sqrt{x^2 + d^2 + z^2 }} \end{bmatrix} \\ |
| + | |
| + | |
| + | \end{alignat} |
| + | </math> |
| + | |
| + | ===Total magnitude=== |
| + | :<math> |
| + | 1 - \frac{d}{\sqrt{x^2 + d^2 + z^2}}\begin{alignat}{2} |
| + | \left( \frac{q}{k} \right)^2 |
| + | & = \left( \frac{x}{ \sqrt{x^2 + d^2 + z^2 }} \right)^2 + \left( \frac{d - \sqrt{x^2 + d^2 + z^2 } }{\sqrt{x^2 + d^2 + z^2 }} \right)^2 + \left( \frac{z }{\sqrt{x^2 + d^2 + z^2 }} \right)^2 \\ |
| + | & = \frac{x^2 + \left( d - \sqrt{x^2 + d^2 + z^2 }\right)^2 + z^2 }{x^2 + d^2 + z^2} \\ |
| + | & = \frac{x^2 + \left( d^2 - 2d \sqrt{x^2 + d^2 + z^2 } + x^2 + d^2 + z^2 \right) + z^2 }{x^2 + d^2 + z^2} \\ |
| + | & = \frac{2 x^2 + 2 d^2 + 2 z^2 - 2d \sqrt{x^2 + d^2 + z^2 } }{x^2 + d^2 + z^2} \\ |
| + | & = 2 \frac{( x^2 + d^2 + z^2 ) - d \sqrt{x^2 + d^2 + z^2 } }{x^2 + d^2 + z^2} \\ |
| + | & = 2 \left( 1 - \frac{d}{\sqrt{x^2 + d^2 + z^2}} \right) \\ |
| + | q & = \sqrt{2}k \sqrt{1 - \frac{d}{\sqrt{x^2 + d^2 + z^2}} } |
| \end{alignat} | | \end{alignat} |
| </math> | | </math> |
Revision as of 13:06, 13 January 2016
In transmission-SAXS (TSAXS), the x-ray beam hits the sample at normal incidence, and passes directly through without refraction. TSAXS is normally considered in terms of the one-dimensional momentum transfer (q); however the full 3D form of the q-vector is necessary when considering scattering from anisotropic materials. The q-vector in fact has three components:

This vector is always on the surface of the Ewald sphere. Consider that the x-ray beam points along +y, so that on the detector, the horizontal is x, and the vertical is z. We assume that the x-ray beam hits the flat 2D area detector at 90° at detector (pixel) position
. The scattering angles are then:
![{\displaystyle {\begin{alignedat}{2}\theta _{f}&=\arctan \left[{\frac {x}{d}}\right]\\\alpha _{f}^{\prime }&=\arctan \left[{\frac {z}{d}}\right]\\\alpha _{f}&=\arctan \left[{\frac {z}{d/\cos \theta _{f}}}\right]\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/facc9ad57cd58f15e7403d40dc08f08815d3662b)
where
is the sample-detector distance,
is the out-of-plane component (angle w.r.t. to y-axis, rotation about x-axis), and
is the in-plane component (rotation about z-axis). The alternate angle,
, is the elevation angle in the plane defined by
.
Total scattering
The full scattering angle is defined by a right-triangle with base d and height
:
![{\displaystyle {\begin{alignedat}{2}2\theta _{s}=\Theta &=\arctan \left[{\frac {\sqrt {x^{2}+z^{2}}}{d}}\right]\\&=\arctan \left[{\frac {\sqrt {(d\tan \theta _{f})^{2}+(d\tan \alpha _{f}^{\prime })^{2}}}{d}}\right]\\&=\arctan \left[{\sqrt {\tan ^{2}\theta _{f}+\tan ^{2}\alpha _{f}^{\prime }}}\right]\\&=\arctan \left[{\sqrt {\tan ^{2}\theta _{f}+{\frac {\tan ^{2}\alpha _{f}}{\cos ^{2}\theta _{f}}}}}\right]\\\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/ce190aa4f7dd836349234c33033cb245c49d4f20)
The total momentum transfer is:
![{\displaystyle {\begin{alignedat}{2}q&={\frac {4\pi }{\lambda }}\sin \left(\theta _{s}\right)\\&={\frac {4\pi }{\lambda }}\sin \left({\frac {1}{2}}\arctan \left[{\frac {\sqrt {x^{2}+z^{2}}}{d}}\right]\right)\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/978ccef9bfce6510674b68221b9f287f94e0bc79)
Given that:
![{\displaystyle {\begin{alignedat}{2}\cos(\arctan[u])&={\frac {1}{\sqrt {1+u^{2}}}}\\\cos(2\theta _{s})&={\frac {1}{\sqrt {1+({\sqrt {x^{2}+z^{2}}}/d)^{2}}}}\\&={\frac {d}{\sqrt {d^{2}+x^{2}+z^{2}}}}\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/07a031cc7bdbb545bcbf2e5d51b1899f74c01e74)
We can also write:

Where we take for granted that q must be positive.
In-plane only
If
(and
), then
,
, and:

The other component can be thought of in terms of the sides of a right-triangle with angle
:

Summarizing:

Out-of-plane only
If
, then
,
, and:

The components are:

Summarizing:

Components (angular)
For arbitrary 3D scattering vectors, the momentum transfer components are:

In vector form:

Total magnitude
Note that this provides a simple expression for q total:

Check
As a check of these results, consider:

And:

Components (distances)
![{\displaystyle {\begin{alignedat}{2}\mathbf {q} &={\frac {2\pi }{\lambda }}{\begin{bmatrix}\sin \theta _{f}\cos \alpha _{f}\\\cos \theta _{f}\cos \alpha _{f}-1\\\sin \alpha _{f}\end{bmatrix}}\\&={\frac {2\pi }{\lambda }}{\begin{bmatrix}\sin \left(\arctan \left[{\frac {x}{d}}\right]\right)\cos \left(\arctan \left[{\frac {z}{d/\cos \theta _{f}}}\right]\right)\\\cos \left(\arctan \left[{\frac {x}{d}}\right]\right)\cos \left(\arctan \left[{\frac {z}{d/\cos \theta _{f}}}\right]\right)-1\\\sin \left(\arctan \left[{\frac {z}{d/\cos \theta _{f}}}\right]\right)\end{bmatrix}}\\&={\frac {2\pi }{\lambda }}{\begin{bmatrix}{\frac {x/d}{\sqrt {1+\left(x/d\right)^{2}}}}{\frac {d}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\\{\frac {1}{\sqrt {1+\left(x/d\right)^{2}}}}{\frac {d}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}-1\\{\frac {z\cos \theta _{f}}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\end{bmatrix}}\\&={\frac {2\pi }{\lambda }}{\begin{bmatrix}{\frac {xd}{\sqrt {d^{2}+x^{2}}}}{\frac {1}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\\{\frac {d}{\sqrt {d^{2}+x^{2}}}}{\frac {d}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}-1\\{\frac {z\cos \theta _{f}}{\sqrt {d^{2}+z^{2}\cos ^{2}\theta _{f}}}}\end{bmatrix}}\\\end{alignedat}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/6ea671cecdf06e0446180db0c1e73d2bb4fd81a5)
Note that
, and
so:

And:

Total magnitude
